Why Do I Follow a Digital Influencer? The Perception of Millennial Women in The Northeast (Management and Connections Journal, 2024)
This study aims to investigate the reasons why millennial women living in the Northeast region follow digital influencers on their social media. This is a qualitative, descriptive study. To this end, 18 semi-structured interviews were conducted with northeastern women from the millennial generation. Based on the analysis below, it was found the reasons that the interviewees take into consideration when following digital influencers: sense of closeness they have with the influencer when he shares real life, entertainment, inspiration to compose looks and interact/trust transmitted by the influencer and replacement. Identity was listed as the most influential reason, presenting the following subcategories: personality, life history, body type, lifestyle, regionalism and/or occupation. Therefore, the present study has theoretical relevance to collaborate with this theme; it is practical to provide managers with information that can serve as a basis for developing marketing strategies.
Keywords: consumer behavior; digital influencers; digital social media; millennial generation